Experimental and numerical investigation of the damping of flax–epoxy composite plates. (15th January 2019) - Mahmoudi, S.; Kervoelen, A.; Robin, G.; Duigou, L.; Daya, E.M.; Cadou, J.M.
Abstract: In this paper, the vibration behaviour and damping performances of Flax Fiber Reinforced Epoxy (FFRE) are investigated. Static tests using FFRE composite beams are carried out leading to the identification of elastic properties of each layer. Then, three FFRE composite plates are elaborated and used in experimental vibration tests to identify their eigenfrequencies and their modal damping. In numerical part, a constant complex representation of the stiffness is assumed and the loss factors are supposed constants and identified from the first experimental vibration mode. The homogenization technique and the finite element method are applied to describe their damped dynamic behaviour. The resolution of the resulting non-linear problem is carried out using the Asymptotic Numerical Method (ANM). Experimental results show that the modal damping is greater when the flax fibers are oriented at 90 ° . Comparing numerical and experimental results, the proposed finite element modelling enables to estimate the damped eigenfrequencies with high accuracy. However, the predicted modal loss factors are over-estimated compared to experimental ones. It is concluded that the present modelling should be improved considering the frequency dependence of damping.